Volume 8: Ocean Renewable Energy 2013
DOI: 10.1115/omae2013-10649
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study for SPAR Type Floating Offshore Wind Turbine With Blade-Pitch Control

Abstract: The experimental proof of the floating wind turbine has been started off Goto Islands in Japan. Furthermore, the project of floating wind farm is afoot off Fukushima Prof. in north eastern part of Japan. It is essential for realization of the floating wind farm to comprehend its safety, electric generating property and motion in waves and wind. The scale model experiments are effective to catch the characteristic of floating wind turbines. Authors have mainly carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Several generations of "thrust-scaled blades" have been applied in wave basins [132,134,135]. These blades are designed with modified chord and airfoil shape, while maintaining tip speed ratio and mass distribution, to obtain correct Froude-scaled thrust forces (Figs.…”
Section: Physical Testingmentioning
confidence: 99%
“…Several generations of "thrust-scaled blades" have been applied in wave basins [132,134,135]. These blades are designed with modified chord and airfoil shape, while maintaining tip speed ratio and mass distribution, to obtain correct Froude-scaled thrust forces (Figs.…”
Section: Physical Testingmentioning
confidence: 99%
“…In 2010, one half-scale and one full-scale semi-type FOWTs were demonstrated in Japan (Ishida et al 2013). The MOE Project (Figure 3) was the first grid-connected FOWT in Japan (100-kW half-scale model) and the fullscale FOWT has also been installed (2 MW).…”
Section: On-site Measurementsmentioning
confidence: 99%
“…Utsunomiya et al (2013a, b) also compared the numerical calculations. In summary, full-scale tests have been conducted at the ocean (Ishida et al, 2013;Utsunomiya et al 2013a, b) and the derivation of their numerical model was provided by Matsukuma and Utsunomiya (2008).…”
Section: Progress Of Model Tests On Fowtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagherieh and Nagamune developed a linear parameter varying controller for FOWT with a barge platform, which is a gain‐scheduled scheme with respect to the wind speed. Chujo et al conduct experimental study on blade pitch control for a lab‐scale FOWT with a spar buoy floater, while Skaare et al reported field test for the Hywind Demo FOWT under different pitch control schemes.…”
Section: Introductionmentioning
confidence: 99%